2013
DOI: 10.1136/bmjqs-2012-001775
|View full text |Cite
|
Sign up to set email alerts
|

Increases in HIV screening in primary care clinics through an electronic reminder: an interrupted time series

Abstract: Implementing an electronic medical record-based reminder effectively increased HIV testing among primary care patients not previously tested, while education and practice feedback alone did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…Study results showed a two-fold increase in overall testing after reminder implementation. These results support the findings of a study from Case Western Reserve University, which showed that a passive EMR reminder decreased the number of patients never tested for HIV, as well as findings from a study at the Veterans’ Administration (VA) system, which showed increased HIV screening after implementation of a comprehensive intervention that included an active electronic reminder [ 10 , 11 ]. An Indian Health Service survey also found that having an electronic reminder in place for more than one year was correlated with higher levels of HIV screening [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Study results showed a two-fold increase in overall testing after reminder implementation. These results support the findings of a study from Case Western Reserve University, which showed that a passive EMR reminder decreased the number of patients never tested for HIV, as well as findings from a study at the Veterans’ Administration (VA) system, which showed increased HIV screening after implementation of a comprehensive intervention that included an active electronic reminder [ 10 , 11 ]. An Indian Health Service survey also found that having an electronic reminder in place for more than one year was correlated with higher levels of HIV screening [ 12 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, a relative strength of our study is the increase in screening it achieved without any of the other time- or resource-intensive interventions described in other positive EMR reminder studies, including provider education [ 11 ], academic detailing and use of champions [ 10 ]. Indeed, our study shows a similar proportional rise in screening to at least one prior study [ 10 ] which was much more resource-intensive.…”
Section: Discussionmentioning
confidence: 99%
“…Processes that depersonalise testing and makes the patient think "that it is offered to all" facilitate and encourage individuals to test and improve testing rates. In this context, the use of electronic flagging on GP computer systems to indicate when a patient should be offered a test could be useful [82]. Such an approach would help to eliminate the perceived view that a judgement is being made by the HCP about an individual's sexuality or race, or that they have been singled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to their simplicity and simple rules for detecting non-random patterns and variation over time, the run chart has been described as the 'universal tool' for virtually every improvement project. 11 They have been employed by clinical teams for a wide variety of health care processes such as HIV screening in primary care, 12 for inpatient bronchiolitis, 13 chemotherapy, 14 measuring inpatient harms, 15 central line associated bacteraemia, 16 orthopaedics, 17 acute coronary syndrome, 18 inhaled corticosteroid prescribing, 19 insulin therapy 20 and also by patients. 5,21 At the time of the study, the two PHOs also used run charts to track immunisation and to illustrate progress towards population health priority areas such as giving brief advice for smoking cessation.…”
Section: Discussionmentioning
confidence: 99%